2012
DOI: 10.1186/1746-1596-7-104
|View full text |Cite
|
Sign up to set email alerts
|

Beta 1 integrin predicts survival in breast cancer: a clinicopathological and immunohistochemical study

Abstract: BackgroundThe main focus of several studies concerned with cancer progression and metastasis is to analyze the mechanisms that allow cancer cells to interact and quickly adapt with their environment. Integrins, a family of transmembrane glycoproteins, play a major role in invasive and metastatic processes. Integrins are involved in cell adhesion in both cell-extracellular matrix and cell-cell interactions, and particularly, β1 integrin is involved in proliferation and differentiation of cells in the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 53 publications
3
55
0
1
Order By: Relevance
“…␤1-Integrin is highly expressed in most tumors and is associated with a negative prognostic significance such as overall and disease-free survival, recurrence, and metastasis for head and neck and squamous cell carcinoma, melanoma, lung, breast, prostate, laryngeal, and pancreatic cancers (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). A recent immunostaining study of 225 breast invasive ductal carcinomas (IDCs) showed that ␤1-integrin was overexpressed in 32.8% of patients with IDCs (13). Numerous studies show that focal adhesion kinase (FAK) which is downstream from ␤1-integrin is also a negative prognostic factor for breast cancer patients (18)(19)(20).…”
mentioning
confidence: 99%
“…␤1-Integrin is highly expressed in most tumors and is associated with a negative prognostic significance such as overall and disease-free survival, recurrence, and metastasis for head and neck and squamous cell carcinoma, melanoma, lung, breast, prostate, laryngeal, and pancreatic cancers (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). A recent immunostaining study of 225 breast invasive ductal carcinomas (IDCs) showed that ␤1-integrin was overexpressed in 32.8% of patients with IDCs (13). Numerous studies show that focal adhesion kinase (FAK) which is downstream from ␤1-integrin is also a negative prognostic factor for breast cancer patients (18)(19)(20).…”
mentioning
confidence: 99%
“…Supporting this model are the results of genomic sequencing approaches which reveal that mutations in a wide range of ECM components, integrins and cytoskeletal components occur in primary breast cancers (Ellis et al, 2012;Shah et al, 2012). Furthermore, activating mutations in b1 integrin increase the susceptibility for tumour formation derived from epithelial cells in the skin, whereas perturbed b1 integrin expression correlates with poor prognosis in breast cancer patients (dos Santos et al, 2012;Ferreira et al, 2009). …”
Section: Integrins and Polarity In Cancermentioning
confidence: 74%
“…In certain types of cancer, β1 integrin is associated with poor prognosis or metastasis, including in prostatic cancer (15,24), melanoma (25), gastric carcinoma (26) and hypopharyngeal squamous cell carcinoma (27). However, in other types of cancer, including breast cancer, studies have reported different or contradictory conclusions (28)(29)(30). This suggests that additional clinical observations and studies are required to understand this association.…”
Section: Metastasismentioning
confidence: 81%